PENGARUH PENGAWASAN TERHADAP EFEKTIVITAS KERJA PEGAWAI (Suatu Studi Tentang Pengaruh Pengawasan Terhadap Efektivitas Kerja Pegawai di SMP Negeri 1 Camplong Kabupaten Sampang) - Mohammad Hamzah (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2019)
The purpose of this study is to determine whether there is an influence of supervision on the work effectiveness of employees at SMP Negeri 1 Camplong, Sampang Regency. quantitative analysis results using the product moment formula, the r count obtained is 0.822 with N = 25, this has proven the correlation between supervisory activities with the effectiveness of employee work in SMP Negeri 1 Camplong, Sampang Regency. Supervision activities carried out by superiors or authorities are apparently quite influential on the effectiveness of employee work, especially in SMP Negeri 1 Camplong, Sampang Regency. In order to create an employee's work effectiveness, clear working rules and a good work plan should be established by a leader that can be used as a measure in determining the success rate of an employee in carrying out his duties and responsibilities in an agency or government institution including in the State Junior High School 1 Camplong Sampang Regency.